Pengaruh Aplikasi Limbah Lumpur Padat (Sludge) Pabrik Kelapa Sawit terhadap Sifat Kimia Tanah Podsolik Merah Kuning di Kotawaringin Barat - Ilham Setiawan; Meldia Septiana; Ratna Ratna (Universitas Lambung Mangkurat, 2020)
Red Yellow Podsolic soil is one type of land that is widespread in Indonesia and can be developed as agricultural or plantation land. Problems that exist in Red Yellow Podsolic soil include low organic matter, infiltration and slow pre-labeling, low porosity which makes the soil tend to be solid, acidic pH, high Al and Fe content and phosphorus deficiency (P). Solid waste (sludge) from a palm oil mill is a suspended sediment from liquid waste and microorganisms from the Wastewater Treatment Plant (WWTP), which can improve soil chemical properties. This study aims to determine the effect application of sludge waste from palm oil mills on decreasing Al-dd and increasing pH in Red Yellow Podsolic soil. Conduct this research in July to August 2019 at the Greenhouse of the Department of Agroecotechnology, Faculty of Agriculture, Lambung Mangkurat University, Banjarbaru, South Borneo. The method used is a completely randomized design (CRD) of one factor, the observed factor is the sludge of the palm oil mill which consists of 5 levels of treatment, repeated 4 times so as to obtain 20 experimental units, namely: S0 control, S1 15 tons / ha (5.55 g / polybag), S2 25 tons / ha (9.26 g / polybag), S3 35 tons / ha (12.96 g / polybag) and S4 45 tons / ha (16.66 g / polybag). The results showed that the application of oil palm sludge solid sludge on the soil chemical properties of Red Yellow Podsolic soil significantly affected the increase in pH, P-available and CEC and reduced Al-dd.